التحري عن فيروس شحوب وتقزم الحمص على محصول الفول في محافظة اللاذقية - إسماعيل, عماد دأود; عباس, نورا جودت (Latakia University Journal -Biological Sciences Series, 2014)
أجري مسح حقلي للتحري عن فيروس شحوب وتقزم الحمص في حقول الفول في بعض مناطق زراعتها في محافظة اللاذقية. جمعت خلال الجولات الحقلية 252 عينة من نباتات عليها أعراض شحوب وتقزم من 54 حقلاً. أظهرت نتائج اختبار بصمة النسيج المناعي (TBIA) وجود فيروس شحوب وتقزم الحمص على نباتات الفول في بعض مناطق زراعتها وقد تباينت نسب الإصابة بالفيروس في العينات المختبرة من الحقول فكانت أعلى نسبة 33.33 % في قرية رأس العين ، وأقلها في قرية البرجان 7.69 %. Afield survey of ckickpea chlorotic stunt virus (CPCSV) was conducted in some plantation areas in Lattakia province. A total of 252 samples were collected from plants showing chlorotic and stunting symptoms from 54 field. Results of Tissue Blot Immunobonding Assay has shown the presence of CPCSV in some plantation areas. The percentage of CPCSV varied in samples collected from fields, the highest percentage was 33.33% in Ras-elain aria and the lowest was 7.69% in Elbourjan aria.